The Surface Layer Homology Domain-Containing Proteins of Alkaliphilic Bacillus pseudofirmus OF4 Play an Important Role in Alkaline Adaptation via Peptidoglycan Synthesis - Fujinami, Shun; Ito, Masahiro (Frontiers in Microbiology, 2018)
It is well known that the Na+ cycle and the cell wall are essential for alkaline adaptation of Na+-dependent alkaliphilic Bacillus species. In Bacillus pseudofirmus OF4, surface layer protein A (SlpA), the most abundant protein in the surface layer (S-layer) of the cell wall, is involved in alkaline adaptation, especially under low Na+ concentrations. The presence of a large number of genes that encode S-layer homology (SLH) domain-containing proteins has been suggested from the genome sequence of B. pseudofirmus OF4. However, other than SlpA, the functions of SLH domain-containing proteins are not well known. Therefore, a deletion mutant of the csaB gene, required for the retention of SLH domain-containing proteins on the cell wall, was constructed to investigate its physiological properties. The csaB mutant strain of B. pseudofirmus OF4 had a chained morphology and alkaline sensitivity even under a 230 mM Na+ concentration at which there is no growth difference between the parental strain and the slpA mutant strain. Ultra-thin section transmission electron microscopy showed that a csaB mutant strain lacked an S-layer part, and its peptidoglycan (PG) layer was disturbed. The slpA mutant strain also lacked an S-layer part, although its PG layer was not disturbed. These results suggested that the surface layer homology domain-containing proteins of B. pseudofirmus OF4 play an important role in alkaline adaptation via peptidoglycan synthesis.